Pengembangan Instrumen Moral Competency Inventory Berbasis Dimensi Moral Pancasila - Fikri Nurcahya; Soeharno Soeharno; Awaluddin Tjalla; Lussy Dwiutami Wahyuni; Yakob KM (Pancasila: Jurnal Keindonesiaan, 2025)
This study aims to develop and validate the reliability of the Moral Competency Inventory based on Moral Dimensions of Pancasila to support the Pancasila Ideology Development Training Program. A total of 356 respondents were involved in this study, selected through convenience sampling from the Pancasila Ideology Development Training Program target group. The study employed 32 statement items designed and validated by eight Subject Matter Experts. Content validation results showed all items had Content Validity Ratio ≥ 0.75 with a Content Validity Index of 0.9. Construct validity was tested using Exploratory Factor Analysis, resulting in four main factors with 24 valid items explaining 55.721% of total variance. Reliability, calculated using Cronbach’s Alpha, produced a value of 0.939, reflecting very high internal consistency. These findings confirm that the instrument is valid and reliable for measuring Pancasila-based moral competencies across various contexts, particularly for the implementation of the Pancasila Ideology Development Training program.